Demographic dynamics of the Belarusian-Russian border regions - Zlotnikov, Anatoly G.; Rybakovskii, Leonid L. (Journal of the Belarusian State University. Sociology, 2020)
The article deals with the demographic dynamics of the border regions of the Russia and Belarus. The article compares trends in population changes in the border Belarusian (Vitebsk, Gomel and Mogilev) and Russian (Bryansk, Pskov and Smolensk) regions over periods of 1959–1989 and 1989–2019. A comparison of the levels of life expectancy of the population at birth in these regions is given. The characteristics of the depopulation coefficient, as well as the effectiveness of the migration movement of the population are given. Their analysis revealed a higher level of demographic dynamics in the Belarusian border regions compared to the Russian regions. However, in general, the demographic dynamics of both Belarusian and Russian regions are characterised by depopulation trends that are typical of other regions with Slavic populations.